Daya Gabung Inbrida Jagung Toleran Cekaman Kekeringan dan Nitrogen Rendah pada Pembentukan Varietas Hibrida - Efendi, Roy; M., Andi Takdir; Azrai, Muhammad (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Low maize grain yield due to drought and low N stresses maybe overcome by growing tolerance hybrid maize varieties. The objectives of this research were to analyze the combining ability of eight inbred lines possessing those traits and indentify suitable parental inbred lines which can be used to develop single cross hybrid tolerant to drought and low nitrogen. Eight inbred lines were crossed using complete diallel cross design of Griffing’s- I on Februry to June, 2014. Those inbred lines were 1044-30, DTPYC9-F46-3-9-1-1-B (for drought tolerance), MR 14 (medium drought tolerance), G20133077 (tolerant to low N), CY 11, CLRCY039 (medium tolerant to low N), and CY12 and G2013631 (for drought and low N sensitive). Fifty-six experimental hybrids derived from diallel crosses, eight inbred lines and four commercial hybrid varieties as checks were evaluated under managed drought, low dosage of N fertilization and under optimum condition, during the dry season (July to October) of 2014. Randomized complete block design three replications was used in each different stress condition. The results showed that CY 11, G2013631, and MR 14 inbred lines possesed good general combining ability (GCA) for grain yield under drought, low N, and optimum conditions. These inbred lines also showed good GCA for the secondary traits such as large stem, delayed leaf rolling and late leaf senescence to support for high grain yield under drought stress and low N condition. Inbred lines of drought and low N sensitive such as G2013631, but had high GCA, could be used as parent to develop drought and low N tolerance hybrids if crossed with inbred lines having medium-tolerant to drought or tolerant to low N, such as G20133077, which had low DGU, or CY11 which had high GCA. Hybrid maize tolerant to drought and tolerant to low N, such as CY11 x G20133077, G20133077 x G2013631, and CY 11 x G2013631, produced significantly higher grain yield, over 8 t/ha, under drought and under low N, as compared with hybrid varieties Bima 3 and Bisi 2, which yielded 5.91 and 6.59 t/ha under drought, and 6.82 and 7.01 t/ha under low N condition. Grain yields under optimum condition were positively correlated with those under both drought and low N conditions. The result suggests that it is possible for improving grain yield of hybrid maize, simultaneously for optimum, drought stress and low N conditions.